2015
DOI: 10.18632/oncotarget.3698
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced tumorigenicity by mitochondrial DNA mild mutations

Abstract: To understand how mitochondria are involved in malignant transformation we have generated a collection of transmitochondrial cybrid cell lines on the same nuclear background (143B) but with mutant mitochondrial DNA (mtDNA) variants with different degrees of pathogenicity. These include the severe mutation in the tRNALys gene, m.8363G>A, and the three milder yet prevalent Leber's hereditary optic neuropathy (LHON) mutations in the MT-ND1 (m.3460G>A), MT-ND4 (m.11778G>A) and MT-ND6 (m.14484T>C) mitochondrial gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 61 publications
2
54
0
Order By: Relevance
“…Since then, several other groups have reported similar findings although using different mtDNA mutations (612). Of interest, one group reported that mild mtDNA mutations were actually more potent at generating aggressive tumors compared to cells carrying mutations causing severe defect in OXPHOS (11). While in most studies the mechanism remained unclear, some have suggested that mtDNA mutations affecting OXPHOS act on invasion via a cross talk between cancer cell mitochondria and the extracellular matrix (12).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other groups have reported similar findings although using different mtDNA mutations (612). Of interest, one group reported that mild mtDNA mutations were actually more potent at generating aggressive tumors compared to cells carrying mutations causing severe defect in OXPHOS (11). While in most studies the mechanism remained unclear, some have suggested that mtDNA mutations affecting OXPHOS act on invasion via a cross talk between cancer cell mitochondria and the extracellular matrix (12).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that cellular proliferation and survival, especially in tumor cells, is also related to Ras, whose activity is dependent on farnesylation [38]. Since 143B cells carry a Ras mutation [31,32] we reasoned that mevinolin-induced reduction of cellular viability could be also related to Ras defarnesylation. Interestingly, while impairment of Ras farnesylation by mevinolin was evident in 143B cells, the highest induction of apoptotic markers, including cleaved Caspase 3 and PARP (Poly (ADPribose) polymerase), was observed in mevinolin-treated MG63 cells (Figure 5c).…”
Section: Mevinolin Effects In Os Cells Are Related To Prelamin a Accumentioning
confidence: 98%
“…However, as compared to other OS cell lines, MG63 showed higher protein levels of lamin A (Figure 2a,b). The lowest lamin A/C levels were determined in HOS cells, and in the 143B Ras-mutated HOS-derived cell line [31,32] (Figure 2a,b). These data were also confirmed in other OS cell lines obtained in our laboratory (Supplementary Figure S1).…”
Section: Lamin A/c Expression Is Reduced In Osteosarcoma Cellsmentioning
confidence: 98%
“…Recent evidence indicates that, by acting at the ETC‐complexes level, certain polyphenols would be able to modulate the rate of mitochondrial superoxide production . The pathogenesis of both neurological disorders and cancer has been related to mitochondrial dysfunction . Mitochondrial dysfunction and consequent energy depletion are the major causes of oxidative stress resulting in alteration of ionic homeostasis and causing loss of cellular integrity.…”
Section: Introductionmentioning
confidence: 99%